O trabalho docente na EAD em Serviço Social em instituições de Ensino Superior privado na região de Ribeirão Preto/SP - Silva, Tatiana Freire da (2020)
This thesis discusses the teaching in Private Institutions of higher education in E-learning mode in Ribeirão Preto/SP region. Its aim is to analyze the conditions and relationships in which this work is done in the private education context of expansion that has taken place in recent years in the country, due to the extensive participation of private companies in education, with a clear definition that these are typical brands market, where education assumes the character of goods. The subject matter turns to the analysis of teachers' working conditions in higher education, profession inserted in the logic of capitalist relations, where these professionals sell their labor power. For this purpose, we sought to apprehend how the current situation of distance higher education determines and characterizes the teaching of social workers in social service programs, problematizing the conditions of precariousness and flexibility of this work. Therefore, there were bibliographical research, documentary and empirical, which highlighted the relevance of having consciousness of the workspace that imposes specific conditions on its formatting and organization, whose main mediation are the information and communication technologies (ICT). For the collection of empirical data, was conducted qualitative research, with the questionnaire based and semistructured interviews based on guiding script. The universe of the research comprehended three (03) private institutions of higher education, that offer distance learning courses (Elearning) in Ribeirão Preto / SP region. The research subjects were six (06) social workers working in undergraduate courses in Social Service. The analysis, based on the studies and research results, pointed out that the main precariousness and flexibility factor in working relationships is related to the adoption of new digital technologies that transformed the nature and ways of performing the teaching work, conditioning it to the mercantile logic of the private initiative with priority purposes of profit